Faktor-Faktor Yang Mempengaruhi Ruptur Perineum Pada Ibu Bersalin Normal di Rumah Sakit Bhayangkara Mappaouddang Makassar Tahun 2014 - Candrayanti, Lilis (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2019)
Background: Perineal rupture is a problem in labor and the second cause of bleeding after uterine atony. According to WHO in 2014 there were 2.7 million cases of Perineal Rupture in maternity mothers. Factors that can cause perineal rupture are parity, distance of birth, baby's weight, birth management is not as it should be, age, extraction, vacuum extraction, and episiotomy. Objective: For Factors Affecting Normal Perineal Rupture. Research Methods: This study is an analytic observational with a